Pendidikan Pluralistik dan Manfaatnya Bagi Peningkatan Nilai Tasamuh (Studi Analisis TerhadapTradisi dan Pengamalan Nilai-Nilai Tasamuh Dikalangan Pemuda Desa Gempol) - R, Rosyadi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research was conducted in the Gempol village community to obtain data on traditions in Gempol and the tolerance attitudes of young people, as well as the benefits of implementing these traditions in fostering tolerance. This research is based on the premise that education is the process of transferring habits, traditions, culture, and skills to the younger generation, who will, in turn, apply them in their daily lives and be held morally accountable. This transfer of habits, traditions, culture, and skills must be positive, such as education in morals, manners, and tolerance. Tolerance itself is an attitude of mutual respect for all differences without condemning them. This attitude of tolerance is crucial given the strong pluralistic and diverse values of the Indonesian nation. This research employed qualitative methods, reviewing books as theoretical material. Data collection methods included interviews, participant observation, and data analysis. The author chose content analysis, or analyzing the content of messages or communications. The data was then analyzed according to the material discussed. Based on the research results, it can be concluded that society, especially youth, strongly upholds pluralistic values, while respecting old traditions without closing the door to new traditions that can benefit them and society. This is evident in the youth's enthusiasm for seminars, cultural dialogues, and social activities, which significantly contribute to instilling a sense of tolerance and tolerance toward the differences that exist within their communities.